Network performance evaluation of tunneling mechanism - Bahaman, Nazrulazhar; Prabuwono, Anton Satria; AlSaqour, Read; Mas'ud, Mohd Zaki (Asian Network for Scientific Information, 2012)
Internet Protocol version 6 (IPv6) is introduced to replace the services offered by the Internet Protocol version 4 (IPv4) and it is aimed to improve the current provisions as well as providing better services to the Internet's users. Several types of IPv6 transition mechanisms have been developed to migrate the IPv4 technology to IPv6 technology. Although all transition mechanisms have the same objective, the process necessitates compliance with their respective capabilities. This paper focuses on the evaluation of the transition mechanisms namely Tunneling Mechanism in terms of data transmission. The evaluation is based on an Experimental work that is conducted on a controlled testbed environment. User-to-user network performance software is used to obtain the throughput, round trip time and tunneling overhead for TCP and UDP transmission protocol. The transition mechanism performance results are then compared with the performance of native IPv4 and IPv6 environment. Â© 2012 Asian Network for Scientific Information.